GENOTYPIC POPULATION STRUCTURE OF ASCOCHYTA PINODES AND PHOMA PINODELLA IN POLAND - Furgał-Węgrzycka, Helena; Węgrzycki, Michał (Plant Breeding and Seed Science, 2009)
The genotypic populations structure of Ascochyta pinodes and Phoma pinodella was de ter mined across a hierarchy of spatial and temporal scale by using vegetative in compatibility system as phenotypic genetic marker. Components of genetic variation within and be tween populations included the following values: in dices of diversity H’, richness (g), indices of evenness E1, E2 and E5, spatio-temporal analysis of genotypic variation (HT and HS val ues), pairwise comparisons of geno type diversity, distribution of VCGs across spatio-temporal scale (GST value) and analysis of variance calculated on VCGs ge no type frequencies within populations...